Effects of two hours of heavy-intensity exercise on the power-duration relationship - Clark, I. E.; Vanhatalo, A.; Bailey, S. J.; Wylie, L.; Kirby, B. S.; Wilkins, B.; Jones, A. M. (Medicine & Science in Sports & Exercise, 2018)
Introduction Changes in the parameters of the power-time relationship (critical power (CP) and W') during endurance exercise would have important implications for performance. We tested the hypotheses that CP and W', estimated using the end-test power (EP) and the work done above EP (WEP), respectively, during a the 3-min all-out test (3MT), can be reliably determined, and would be lower, after completing 2 h of heavy-intensity exercise.